2017
DOI: 10.1016/j.cortex.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal lobar degeneration and social behaviour: Dissociation between the knowledge of its consequences and its conceptual meaning

Abstract: Inappropriate social behaviour is an early symptom of frontotemporal lobar degeneration (FTLD) in both behavioural variant frontotemporal dementia (bvFTD) and semantic dementia (SD) subtypes. Knowledge of social behaviour is essential for appropriate social conduct. The superior anterior temporal lobe (ATL) has been identified as one key neural component for the conceptual knowledge of social behaviour, but it is unknown whether this is dissociable from knowledge of the consequences of social behaviour. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
2
25
0
1
Order By: Relevance
“…Aberrant top-down control may promote inflexible behavioural routines: e.g., food consumption is normally heavily modulated by social mores; where relevant social knowledge is no longer accessible, the imperative to consume available food is likely to lead to faux pas. This interpretation, emphasising a deranged social lexicon rather than a release of frontal controls, is supported by neuropsychological evidence 27 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Aberrant top-down control may promote inflexible behavioural routines: e.g., food consumption is normally heavily modulated by social mores; where relevant social knowledge is no longer accessible, the imperative to consume available food is likely to lead to faux pas. This interpretation, emphasising a deranged social lexicon rather than a release of frontal controls, is supported by neuropsychological evidence 27 .…”
Section: Discussionmentioning
confidence: 83%
“…Semantic dementia (SD) is the paradigmatic disorder of the human semantic memory system, characterised by selective, progressive erosion of the meanings of words, sensory objects and concepts [20][21][22][23][24] . Patients typically present with insidious anomic aphasia and loss of vocabulary but as the syndrome evolves, semantic impairment blights all sensory modalities and complex behavioural disturbances supervene, due to impaired understanding and evaluation of socio-emotional signals [25][26][27] . The SD syndrome arises from pathogenic protein deposition; principally targeting one canonical, large-scale connectivity network: the 'semantic appraisal network' .…”
mentioning
confidence: 99%
“…Overall, the typical clinical presentation of right svPPA patients is characterized by behavioral symptoms (e.g., cold interpersonal behavior, loss of empathy) and difficulty with person identification and semantic knowledge for persons (Gorno-Tempini et al, 2004; Snowden et al, 2012; Thompson, Patterson, & Hodges, 2003), with less severe naming deficits and surface dyslexia compared to left svPPA cases (Binney et al, 2016). Consequently, the left temporal lobe has been associated with processing of words and objects (Hodges et al, 1992; Mummery et al, 2000), while the right appears to be associated with processing of socio-emotional stimuli (Rankin et al, 2006; Zahn et al, 2009, 2017). Given the known interplay between handedness and lateralization of domain specific areas (Willems, Peelen, & Hagoort, 2009), the picture is further complicated by the evidence of increased non-right-handedness in svPPA population (Miller et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been suggested that the right temporal lobe binds sensory representations recruited for social and emotional processes due to its connections with the limbic system (Oishi et al, 2015; Olson et al, 2007). This would explain the combination of deficits in person identification and impairments in social and behavioral domains observed in patients with damage to the right temporal atrophy, including bvFTD and right variant of svPPA (Kumfor and Piguet, 2012; Rankin et al, 2006; Zahn et al, 2009, 2017). Recognizing a face as familiar has cognitive implications (promoting retrieval of person-specific information), as well as behavioral ramification (allowing selection of the appropriate course of action) and emotional consequences (impacting social interaction and personal feelings).Therefore, a second line of research would investigate possible correlations between patients’ performance in familiarity judgment tasks and measures of social cognition, such as emotional face comprehension (Rosen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the original formulations of the “Default Mode Network” based on positron emission tomography included the superior ATL(32). Our focus on the right superior ATL is based on its predominance for socio-emotional functions(30, 33) (22, 30, 34-36) relative to the left ATL. This concords with the efficacy of right temporal electroconvulsive therapy in MDD(37), response to which was predicted by right ATL-frontal connectivity including the SCC(38).…”
Section: Introductionmentioning
confidence: 99%